VD_FINDINFO HC / 2010 / 304 vom 25. März 2010 - VD Tribunal cantonal (2010)
PRÉSOMPTION D'INNOCENCE, BRIGANDAGE, AGRESSION, RIXE | 47 CO, 134 CP, 140 CP, 46 al. 1 CP, 46 al. 2 CP, 411 let. g CPP, 411 let. i CPP, 415 CPP